Satellite-Based Monitoring of Spatiotemporal Changes in Batudulang Forest in Sumbawa, Indonesia - Muslim, Mohammad; Witarto, Arief Budhi; Indrajaya, Wahyu (Makara Journal of Technology, 2018)
Space-based earth observation technology applicable to forest inventory and monitoring is well known in the scientific community. High-resolution satellite images form an important data source for forest mapping and change detection at regional and national scales. The value of forest change information derived from remote sensing data is significantly enhanced if this information is integrated into a spatially explicit geographic information system. Satellite-based rapid assessment was conducted to measure spatiotemporal changes in Batudulang forest over the years. The general approach to quantify change in the spatial aspect of the forest involved change detection using moderate-resolution imaging spectro-radiometer satellite-based normalized difference vegetation index. A further top–down approach using high-resolution data from Google Earth was used to complement the mapping and specifically identify areas of spatial, temporal, and thematic change on a grid basis (1×1 sq. km.). Results from change detection studies revealed that the forest area changed from 287 sq. km. in 2008 to 189 sq. km. in 2016. Visual image interpretation of high-resolution Google Earth images (2001–2013) analyzed 63 grids, of which 30 showed significant change and 33 exhibited no change.